STEPS AND PATTERNS TO RELEASE SMALL TRADERS FREE FROM RENTENDENT RELIABILITY (CASE STUDY IN TANJUNG MARKET, MOJOKERTO) - Widiasari, Susi; Sulistyawan, Arie (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2021)
The purpose of this study is to determine the steps and patterns so that market traders can be free of debt and no longer have a dependence on loan sharks. Small traders who are in Tanjung Market, Mojokerto are the variables used in this study. Through the qualitative descriptive method used to analyze data. Among the focus of the study in this study are efforts to understand the capital needs of traders, the government's efforts to overcome the practice of rent-seeking, the various practices carried out by â€œmoneylendersâ€ and the role of financial institutions around the location of â€œloan sharks.â€ The results of this study can be drawn: first, when borrowing money from Tanjung market traders, Mojokerto is not so interested in borrowing from banks and other capital-giving institutions but they are more interested in borrowing from loan sharks, the main cause of their dependence on borrowing from moneylenders, namely the ease with which traders can get capital Second, coordination is needed between the government, Baznas, financial institutions and traders of the Tanjung market, Mojokerto. To unify the vision, mission, and objectives so that traders can be free from debt and not depend on